Vida Saludable: Cuidarse Desde la Cabeza a los Pies - Jennifer Hillan (EDIS)
FCS8821-Span, a 2-page fact sheet by Jennifer Hillan, is the Spanish version of "Healthy Living: Taking Care from Head to Toe" (FCS8821/FY886). It reminds patients with diabetes about the special precautions they need to take to protect their skin, eyes, teeth, gums, and feet and gives tips for keeping these parts of the body healthy. Published by the UF Department of Family, Youth and Community Sciences, January 2007.